Drug interactions and contraindications (Henry Stewart Talks, 2025)
Drug interactions & contraindications, PK/PD mechanisms, Synergistic vs antagonistic effects, Absolute & relative contraindications, Minimizing drug-related harm, Monitoring & risk assessment, Patient education & pharmacovigilance